PELATIHAN METODE PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KEMATANGAN KARIR SISWA - ICHWANUL MUSTAKIM; I MADE SONNY GUNAWAN; REZA ZULAIFI; HARDIYANSYAH HARDIYANSYAH (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of carrying out this community service activity is to assist guidance and counseling teachers or school counselors in improving their competence to provide classical services to students. The activities carried out in this service are in the form of training in the application of Contextual Teaching and Learning learning methods. As for this training activity, it is hoped that guidance and counseling teachers can optimize classical services to deliver material about careers so that students become more mature in understanding their careers. Participants in this training activity were attended by 5 guidance and counseling teachers at SMA Negeri 3 Mataram. The results of this community service show the active participation of the guidance and counseling teachers which can be seen from their enthusiasm in receiving the delivery of material from resource persons. Furthermore, to see the effectiveness of the training activities, it is followed by a teaching simulation session where guidance and counseling teachers or school counselors take turns conducting teaching simulations by applying the Contextual Teaching and Learning method. As for the results of observations, it was found that guidance and counseling teachers had applied the Contextual Teaching and Learning method well in class to students in conveying material related to student careers. ABSTRAKTujuan dilakukannya kegiatan pengabdian masyarakat ini adalah untuk membantu para guru bimbingan dan konseling atau konselor sekolah di dalam meningkatkan kompetensinya untuk memberikan layanan klasikal kepada siswa. Kegiatan yang dilakukan dalam pengabdian ini adalah dalam bentuk pelatihan penerapan metode pembelajaran Contextual Teaching and Learning. Adapun melalui kegiatan pelatihan ini diharapkan para guru bimbingan dan konseling dapat mengoptimalkan layanan klasikal untuk menyampaikan materi tentang karir sehingga siswa menjadi lebih matang dalam pemahaman karirnya. Peserta dalam kegiatan pelatihan ini diikuti oleh 5 orang guru bimbingan dan konseling di SMA Negeri 3 Mataram. Hasil dari pengabdian masyarakat ini menunjukkan partisipasi aktif dari guru bimbingan dan konseling di mana dapat terlihat dari sangat antusiasnya di dalam menerima penyampaian materi dari narasumber. Lebih lanjut, untuk melihat keefektifan dari kegiatan pelatihan maka dilanjutkan dengan sesi simulasi mengajar dimana para guru bimbingan dan konseling atau konselor sekolah secara bergantian melakukan simulasi mengajar dengan menerapkan metode pembelajaran Contextual Teaching and Learning. Adapun berdasarkan hasil observasi diperoleh data bahwa guru bimbingan dan konseling sudah menerapkan metode pembelajaran Contextual Teaching and Learningdengan baik di kelas terhadap siswa dalam menyampaikan materi terkait dengan karir siswa.